Impact of Halal Supply Chain Management on Halal Integrity in Malaysia's TVET Food Industry - Mohamed, Yusaini Hisham; Abdul Fattah, Mohd Faiq; Hassan, Abdul Mutalib; Rani, Mohd Husaini; Puteh, Fadilah (Journal of Technical Education and Training, 2024)
Ensuring the integrity of halal food is among the concerned issues of many Muslim consumers around the world especially on the authenticity of halal food products status. They are keen to know all the activities involved whether the products they purchase are genuinely halal along the supply chain. Although the issue of halal integrity is widely discussed within the halal food industry, the factors attract the attention of both the academic and halal practitioners remain ambiguous. Thus, this paper intends to assess the existing halal food supply chain management (HFSCM) and its influence on halal integrity assurance (HIA). Using quantitative approach, an industry pilots were empirically experimented to test the concepts and provide practical solutions for halal industry players to optimize their HIA in food and beverages (F&B) industries. The survey data was acquired from 121 halal F&B industries. Multiple linear regression technique was used to analyze the data. It was found that the HFSCM of F&B industries have a direct impact on HIA. The findings are set out to argue that new solutions are required to reduce the vulnerability for better optimization of HFSCM thus enhancing the HIA. Significantly, this study seen Technical and Vocational Education and Training (TVET) is critical in ensuring the sustainability of HFSCM especially to cater demands among Muslim population.